2019
DOI: 10.3390/jcm8050566
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of 5015 Salivary Gland Neoplasms Registered in the Hiroshima Tumor Tissue Registry over a Period of 39 Years

Abstract: Salivary gland neoplasms are uncommon, and their epidemiology in Japan has not been well described. We conducted a retrospective review of salivary gland tumors registered in the Hiroshima Tumor Tissue Registry over a period of 39 years. The subjects were 5015 cases ranging in age from 6 to 97 (mean, 54.3) years old. The incidence of both benign tumors and malignant tumors increased with age until 60–69 years and then declined. Among the 5015 salivary gland neoplasms, 3998 (80%) were benign and 1017 (20%) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
54
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 20 publications
17
54
2
6
Order By: Relevance
“…Submandibular gland and minor salivary gland tumors are seen at similar rates. In large series of studies on this subject, their incidence has been reported as between 61%-83% for parotid gland tumors, 10%-17% for submandibular gland tumors, and 3%-26% for minor salivary gland tumors [5][6][7][8][9][10][11][12][13][14][15]. Sublingual gland tumors account for less than 1% of all tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Submandibular gland and minor salivary gland tumors are seen at similar rates. In large series of studies on this subject, their incidence has been reported as between 61%-83% for parotid gland tumors, 10%-17% for submandibular gland tumors, and 3%-26% for minor salivary gland tumors [5][6][7][8][9][10][11][12][13][14][15]. Sublingual gland tumors account for less than 1% of all tumors.…”
Section: Discussionmentioning
confidence: 99%
“…They can be seen in both sexes. Approximately 80% of the tumors are in benign character, and the majority of them are seen in the parotid gland [5]. Although, in many studies, the most commonly seen benign and malignant tumors are reported as pleomorphic adenoma and mucoepidermoid carcinoma, respectively, different tumor types and different rates may be observed in different geographic areas and ethnic groups.…”
mentioning
confidence: 99%
“…In addition, it must also be mentioned that in low‐income locations, individuals often encounter difficulties in the access to healthcare services, 39,40 which may have underestimated the results. Low life expectancy in some countries may also have also underestimated prevalence rates since MEC is more commonly found in individuals with more than 50 years 3,4,23 …”
Section: Discussionmentioning
confidence: 99%
“…Overall, compared to major salivary gland tumors, a higher frequency of malignant neoplasms is reported within minor salivary gland tumors (MiSGT) 3 . Palate, oral mucosa, and lips are usually the most affected sites 3,4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation